A biopolymer-based pH indicator film for visually monitoring beef and fish spoilage. (April 2022) - Sobhan, Abdus; Muthukumarappan, Kasiviswanathan; Wei, Lin
Abstract: Food safety is a worldwide public concern that has recently gained increased attention due to the emerging outbreaks of foodborne diseases. Therefore, there is a pressing need to make simple, cost-effective, and environmentally friendly methods for detecting food spoilage and to mitigate the impact of possible outbreaks. The aim of this study is to develop a biodegradable indicator film which was made by combining cellulose-nanofiber/chitosan dyed with methyl red synthesis (CCM) as a pH indicator film and followed by a single layer coating of polylactic acid (PLA) on its surface, named PLA/CCM film. The microstructural properties of PLA/CCM films were studied using scanning electron microscopy (SEM) and results showed that PLA effectively adhered to the surface of CCM film. The microbial response to PLA/CCM film was determined via a bacterial plating method. It was found that the contact of film with the microbes caused a substantial color change in the film. The coating of PLA upon the CCM film decreased the percentage of the water vapor transmission rate (WVTR). The color of the film vividly altered from slightly red to yellow in response to a pH change in the range of 4–8. The PLA/CCM film was applied to monitor the spoilage of beef and fish at room temperature (23 °C) and revealed the onset of food spoilage by displaying the color change from red to yellow after 1 day. The total viable counts (TVC) of microorganisms and pH of the tested beef sample were determined, and the results revealed that both TVC and pH increased concurrently after beef spoilage. Highlights: The pH indicator film (PLA/CCM) was developed for intelligent food packaging. PLA/CCM indicator film revealed visual color sensitivity to pH changes. The indicator film was applied for real-time monitoring of beef and fish spoilage. The indicator films showed a high potential for monitoring beef spoilage.